Experimental and Numerical Study the Linear Stress Analyses for the Prediction of Fracture Toughness of Ductile Material - Khudair, Sara A.; Taha, Atheed H.; Nassar, Ameen A. (Basrah Journal for Engineering Sciences, 2023)
The purpose of this paper is to determine a stress intensity factor experimental and numerically in the linear region by using a CT specimen of ductile material with a thickness of 15 mm, a width of 30 mm, and pre-crack 1.3 mm this dimension according to ASTM-E399-12 [1], by pulling the specimen in a 600 kN universal testing machine at a very slow speed rate of 0.5 mm/min. The load is applied until the fracture is accrued, the computer-controlled universal testing machine gives the value of the load and the displacement transducer gives a crack mouth opening displacement. The result showed experimental K I is equal to 75.412 MPa √ m, and numerical K I is equal to74.576 MPa √ m, this test showed a very slight decrease in FEA stress intensity factor compared to that in an experimental result which means the stress intensity factor, K I remains very close between experimental and numerical with an error percentage of about (1.12 %). The finite element analysis provides the best approximation to true fracture toughness values, and it can be used to acquire close parameters if experimental testing is not possible.